Austerlitz - Sebald, W. G (Penguin Books, 2001)
He wa "Austerlitz, the internationally acclaimed masterpiece by "one of the most gripping writers imaginable" ("The New York Review of Books), is the story of a man's search for the answer to his life's central riddle.